SSVEP and ERP measurement of cognitive fatigue caused by stereoscopic 3D - Mun, Sungchul; Park, Min-Chul; Park, Sangin; Whang, Mincheol (ELSEVIER IRELAND LTD, 2012)
The purpose of this study was to identify steady-state visually evoked potential (SSVEP) and event-related potential (ERP) correlates of 3D cognitive fatigue. Twenty-one participants (11 females) were subjected to a cognitive test before and after being exposed to a stereoscopic 3D environment. They were categorized into two groups, fatigued and unfatigued, based on their response times and subjective data. The fatigued group exhibited significantly reduced P600 amplitudes and delayed P600 latencies in the post-viewing condition compared to those in the pre-viewing condition. Significant fatigue effects for the fatigued group were also observed at P-4 and O-2 sites during the 8.57 Hz attended task; attend/ignore ratios in this cortical hemisphere after 3D viewing were smaller than those before 3D viewing. (C) 2012 Elsevier Ireland Ltd. All rights reserved.
Keywords: STEADY-STATE; VISUAL FATIGUE; POTENTIALS; ATTENTION; COMFORT